Chinese loans to African countries differ from western development loans - Lorenz Meister; Lukas Menkhoff; Annika Westen (DIW Weekly Report, 2023)
Over the past 20 years, China has granted a conspicuous amount of loans to African countries. New loan data show that compared to Western multilateral loans, Chinese loans have relatively high interest rates and shorter maturities, tend to be highly collateralized, and are volatile over time. Thus, Western loans are generally more likely to be in the economic interest of the borrowing country. Furthermore, Chinese loans are focused on resource-rich countries that undertake fewer anti-corruption efforts, so local policymakers have more opportunities to feather their own nest. Finally, unlike Western loans, Chinese loans are not tied to any economic policy conditions. It seems worth considering for Western lenders to reduce the number and intensity of loan conditions to respect the sovereignty of the borrowing countries.
Keywords: G15; 330; International lending; conditionality; China; Africa